Political Broker Giving Money and Intimidating in Regional Head Elections in Indonesia - Mohammad Hidayaturrahman; Sudarman Sudarman; Naili Adilah Hamhij; Anak Agung Putu Sugiantiningsih; Ahmad Hasan Ubaid; Elazhari Elazhari (Jurnal Politik Indonesia: Indonesian Political Science Review, 2023)
This study was conducted to reveal the models of political brokers and their operating patterns in regional head elections in Indonesia. This research used descriptive qualitative method. Data was collected through in-depth interviews with informants who were directly involved in the regional head election. From the research conducted, it is found that political brokers in regional head elections in Indonesia are village heads, and community leaders. Political brokers perform their role in two ways. First, by giving money to the head of the electorate. The money comes from regional head candidates who are given by the winning team for regional head candidates for political brokers. The money given by regional head candidates to political brokers consists of money for own political broker and operational money, as well as money to be distributed to voters. Second, political brokers also act to intimidate, threaten and frighten potential voters, if they do not vote for candidates who are supported by political brokers.